Mediterranean Diet as a Tool to Combat Inflammation and Chronic Diseases. An Overview - Tsigalou, Christina (Biomedicines, 2020)
Since ancient times, the quality of nourishment is a milestone for the maintenance of health and as it is stated ‘prevention is better than cure’, amongst the so-called ‘healthy’ diets Mediterranean diet (MD) claims the lion’s share. It stands in good stead because of a variety of valuable macro- and micronutrients. So, adherence to a MD is associated with the reduction of inflammation and non-communicable (NCD) OR chronic diseases. Numerous studies try to scrutinize the role of MD components as regards reducing inflammation, lowering rate, and mortality for disorders and illnesses, and preventing NCD. MD regime of the inhabitants of the Mediterranean basin includes a variety of ethnic nutritional habits and regulates an array of effects and epigenetic changes that affect human wellbeing. The research is still ongoing and endeavors to elucidate every aspect of this issue. This review focuses on the impact of MD on inflammation highlights positive results regarding NCD and indicates the need for more high-quality experiments and trials in order to overcome any discrepancies.